представьте выражение в виде многочлена: 1) (2x-y)(y+2x)+x(4-3x) 2)...

0 голосов
91 просмотров

представьте выражение в виде многочлена:

1) (2x-y)(y+2x)+x(4-3x)

2) (y-2)(y+2)+(3-y)(3+y)

3) (a+b)(a-b)-(a-b)^2


Алгебра (57.1k баллов) | 91 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

1) (2x-y)(y+2x)+x(4-3x) = (2x)² - y²  + 4х - 3х² =² - y²  + 4х - 3х² = х² - y² + 4х

2) (y-2)(y+2)+(3-y)(3+y) = -2² +  -y² =  -2² +    = -4 + 9 = 5

3) (a+b)(a-b)-(a-b)² = a²-b² - (a²-2ab + b²) = - b² - + 2ab - b² =

= 2ab - 2

(18.9k баллов)
0 голосов

1) (2x-y)(y+2x)+x(4-3x)=2xy+4x^{2}-y^{2}-2xy+4x-3x^{2}=(4x^{2}-3x^{2})+(2xy-2xy)-y^{2}+4x=x^{2}-y^{2}+4x

 

2) (y-2)(y+2)+(3-y)(3+y)=y^{2}-4+9-y^{2}=(y^{2}-y^{2})+(9-4)=5

 

3) (a+b)(a-b)-(a-b)^{2}=a^{2}-b^{2}-(a^{2}-2ab+b^{2})=a^{2}-b^{2}-a^{2}+2ab-b^{2}=(a^{2}-a^{2})+2ab+(-b^{2}-b^{2})=2ab-2b^{2}

(172k баллов)